New furan derivatives from Annulohypoxylon spougei fungus. Issue 10 (3rd October 2022) - Pimjuk, Preeyanuch; Noppawan, Pakin; Katrun, Praewpan; Mongkolthanaruk, Wiyada; Suwannasai, Nuttika; Tanaka, Junichi; McCloskey, Sirirath
Abstract: Two new furan derivatives, annulofurans A-B (1 –2 ), together with six known compounds were isolated from Annulohypoxylon spougei fungus. The structures were determined based on NMR and mass spectrometry data. The absolute configurations of annulofurans A-B were determined by Electronic Circular Dichroism (ECD) experiment and comparisons with the experimental ECD spectra of synthesized stereoisomers. The evaluation of the effects on radish and ruzi grass radicle elongation by the isolated compounds showed that annulofuran A affected radicle elongation of ruzi grass. The known 2-hydroxyphenylacetic acid methyl ester (7 ) had significant effects against both radish and ruzi grass radicle elongation, which were comparable to the commercial herbicide, glyphosate. Graphical abstract: UF0001